Design and analysis of energy-efficient solar panel cooling system using computational fluid dynamics. Issue 1 (April 2021) - Vaishnav, Sarthak; Kapadiya, Vivek; Harish, R.; Mohan, R.
Abstract: This paper highlights the design of an effective liquid cooling system that utilizes the heat generated from the solar panel as a cooling medium to maintain the optimal desired temperature of the solar panel. The coolant for this finned cooling system is selected based on its vaporizing temperature range and thermal cycle characteristics. For analysis purposes, a CAD model is generated in Solidworks CAD package, and further meshing and numerical simulations are performed using Ansys Fluent software. Flow and heat transfer characteristics of the cooling system are investigated by plotting stream functions, velocity, and temperature distributions inside the system. Probing of variations in temperature, pressure and turbulent kinetic energy along vertical as well as longitudinal direction is graphically analysed. Thus, elucidating characteristic of parametric conditions under observation. This study's results can be the potential background for designing an efficient solar panel cooling system with superior thermal performance.